Vouch for this! : Defunding private interests, defending public schools - Poetter, Thomas S. 1962-; Abodunrin, Abayomi Samuel; Acheampong, Emmanuel; Bizzell, Cerelia V.; Craig, Carolyn S.; Dzimbiri, Mastano N. W.; Fatima, Tahreem; Hughes, Chiquita M.; Kerr, Elizabeth Rae; Pope, Shawnieka E.; Robinson Thompson, Dormetria; Song, Dongxia; et al. (Emerald Publishing Limited : IAP | Information Age Publishing Inc., 2023)
"Vouch for This! Defunding Private Interests, Defending Public Schools (A Call to Action) is an effort by doctoral students in Educational Leadership and their professor to understand and challenge the voucher and charter school movements in Ohio and beyond. Using a curriculum studies approach focusing on autobiographical analysis and a policy advocacy framework, students in a course on the topic shared a common reading list, storied their connections to the current movements in the field, and developed treatments of key aspects of current policy and practice in the areas of voucher and other privatizing efforts in education today embodied in charter schools, homeschooling, and private school settings. Using the tools of currere and policy advocacy as a scholarly community, the authors tackle the multi-faceted challenges and dangers posed by the neoliberal, privatizing movements taking rapid shape across our public school system, as private schools, charters, and homeschooling continue to receive significantly more and more public taxpayer funds to operate and build. The authors share what they learned about the continued demise of public education at the hands of politicians and privateers in Ohio and beyond, and what they think citizens can do to resist. Together in teams, the authors engage topics related to education and public schooling as key aspects of democratic life, the actions taken by capital interests that seize on tragedy and perceived community weakness to privatize education and villainize public schools, the greed that creates fervor and interest in "choice," and suggest ways to take action to stem the tide. The book's foreword is written by well-known education activist William L. Phillis, Executive Director of The Coalition for Equity and Adequacy of School Funding (Ohio E&A), whose coalition of public school districts in Ohio is challenging the constitutionality of the voucher movements with their public case, "Vouchers Hurt Ohio.""-- Provided by publisher.
Keywords: Educational vouchers -- United States -- Evaluation.; Charter schools -- United States -- Evaluation.; Education -- Schools -- Types -- Charter.; Independent schools, private education.; elektronické knihy; electronic books